Analisis Faktor yang Berhubungan dengan Partisipasi Suami dalam Menjaga Kesehatan Kehamilan di Wilayah Kerja Puskesmas Gading Rejo Kabupaten Pringsewu - Aprina, Aprina; Aziza, Nurul (Politeknik Kesehatan Tanjungkarang, 2017)
Husband's role during pregnancy is very important. Participation and support of husband were affect psychosocial aspects. Maternity ladies must be accompanied by a trusted person and make her comfortable during childbirth (Bobak, 2005). This study design was analytical survey approach Cross Sectional. Population were all a husband whose wife was pregnant trimester III in working area Gading Rejo Health Centre, Distric Pringsewu, in Januari to June 2016, as much as 273 peoples. Total sampel were 121 peoples. The research instruments were used questionnaires. Multivariate analyzes were used multiple regression logistic. There was a relationship of knowledge (p-value=0,002 OR=3.688), attitude (p-value=0,030 OR=2521), education level (p-value=0,020OR=2.815), employment (p-value=0,007OR=4351), and income (p-value=0,000 OR=6.981) with the participation of husband. The variable income was the most dominant variable related to the husband's participation in the health of wife's pregnancy (p-value=0.000OR=7142).